Effects of Hardwood Biochar on Methane Production, Fermentation Characteristics, and the Rumen Microbiota Using Rumen Simulation - Teoh, Rebecca; Caro, Eleonora; Holman, Devin B.; Joseph, Stephen; Meale, Sarah J.; Chaves, Alex V. (Frontiers in Microbiology, 2019)
Biochar is a novel carbonised feed additive sourced from pyrolyzed biomass. This compound is known to adsorb gases and carbon, participate in biological redox reactions and provide habitat biofilms for desirable microbiota proliferation. Therefore, biochar holds potential to modify rumen fermentation characteristics and reduce enteric CH4 emissions. The objective of this study was to investigate the effect of hardwood biochar supplementation on fermentation parameters, methane (CH4) production and the ruminal archaeal, bacterial, and fungal microbiota using the in vitro RUSITEC (rumen simulation technique) system. Treatments consisted of a control diet (oaten pasture: maize silage: concentrate, 35:35:30 w/w) and hardwood biochar included at 400 mg or 800 mg per day (3.6% and 7.2% of substrate DM, respectively), over a 15-day period. Biochar supplementation had no effect (P ≥ 0.37) on pH, effluent (mL/d), total gas (mL/d), dry matter (DM) digestibility or CH4 production (mg/d). The addition of 800 mg biochar per day had the tendency (P = 0.10) to lower the % of CH4 released in fermentation compared to 400 mg/d biochar and control treatments. However, no effect (P ≥ 0.44) was seen on total VFA, acetate, propionate, butyric, branched-chain VFA, valerate and caproate production and the ratio of acetate to propionate. No effect (P > 0.05) was observed on bacterial, archaeal or fungal community structure. However, biochar supplementation at 800 mg/d decreased the abundance of one Methanomethylophilaceae OTU (19.8-fold, P = 0.046) and one Lactobacillus spp. OTU (31.7-fold, P < 0.01), in comparison to control treatments. Two fungal OTUs classified as Vishniacozyma victoriae (5.4 × 107 increase) and Sporobolomyces ruberrimus (5.4 × 107 fold increase) were more abundant in the 800 mg/d biochar samples. In conclusion, hardwood biochar had no effects on ruminal fermentation characteristics and may potentially lower the concentration of enteric CH4 when included at higher dosages by manipulating ruminal microbiota abundances.